Research on the Power Flow of Distributed Generation Based on Micro-grid Experiment Platform - LI Zhiyong; WU Binbin; WU Hengliang; LI Yao (Kongzhi Yu Xinxi Jishu)
The access of a large number of distributed sources or the change of those sources’s operation status will cause power flow and node voltage change, and influence their own transient response feature of voltage drop. Therefore, a micro-grid which includes distributed photovoltaic and wind power simulation units was taken as an actual object. It established distributed generation model and network model, and performed simulation process by Newton-Raphson power flow algorithm. The error between the measured data and the theoretical data turned out to be less than 3%. Futhermore, it regulated output power of the controllable generation unit, and analyzed the voltage oscillation and lowvoltage ride-through based on grid-voltage drop simulated by grid simulator. Test results show that the platform can provide semi-physical simulation basis for the research on power flow in distributed generation system.